2016
DOI: 10.1007/s40314-016-0364-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of anthropogenic carbon dioxide emissions through technological options: a modeling study

Abstract: The anthropogenic emission of carbon dioxide (CO 2 ) is the prime culprit for the menace of global warming. To achieve the goal of mitigation of global warming, it is crucial to curb the anthropogenic carbon dioxide emissions. The prime anthropogenic source of CO 2 is fossil fuel burning. In this paper, we propose a nonlinear mathematical model to study the impact of technological options, used for the reduction of CO 2 emissions from fossil fuel burning and industrial processes, on the control of atmospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In recent decades, several mathematical models are used to study the dynamical relationship of atmospheric 0.1emCO2 gas with forest, human population, and so on (Caetano et al, 2011; Devi & Gupta, 2018, 2020; Devi & Mishra, 2020; Misra & Verma, 2013, 2015; Misra et al, 2015; Shukla et al, 2015; Verma & Misra, 2018). Shukla et al (2015) studied the effect of using liquid species and planting green belt around the source on the reduction of 0.1emCO2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, several mathematical models are used to study the dynamical relationship of atmospheric 0.1emCO2 gas with forest, human population, and so on (Caetano et al, 2011; Devi & Gupta, 2018, 2020; Devi & Mishra, 2020; Misra & Verma, 2013, 2015; Misra et al, 2015; Shukla et al, 2015; Verma & Misra, 2018). Shukla et al (2015) studied the effect of using liquid species and planting green belt around the source on the reduction of 0.1emCO2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of initial parameter values was guided by the fulfillment of conditions outlined in the qualitative analysis section. In addition to the data-driven parameter estimation, values of 11 , 5 and 750000 were obtained from [31] , [18] and [32] respectively. For the intrinsic human population growth rate ( r ), data from [23] was considered, where a range of 0.02 to 0.03 per year is considered [31] .…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Sundar et al [14] use optimization to control the atmospheric CO2 level involves managing both the emission rate of CO2 from energy generation and the growth rate of energy consumption. Verma and Misra [15] revealed that by enhancing both the implementation rate and efficiency of technological solutions, a notable reduction in the atmospheric CO2 level can be achieved. By using optimization, the author creates a strategy that minimizes the CO2 emission rate along with the cost associated with the implementation of technologies.…”
Section: Introductionmentioning
confidence: 99%